Purification of a Low Molecular Weight Fucoidan for SPECT Molecular Imaging of Myocardial Infarction - Saboural, Pierre (MDPI, 2014)
Fucoidans constitute a large family of sulfated polysaccharides with several biochemical properties. A commercial fucoidan from brown algae, containing low molecular weight polysaccharidic species constituted of l-fucose, uronic acids and sulfate groups, was simply treated here with calcium acetate solution. This treatment led to a purified fraction with a yield of 45%. The physicochemical characterizations of the purified fucoidan using colorimetric assay, MALLS, dRI, FT-IR, NMR, exhibited molecular weight distributions and chemical profiles similar for both fucoidans whereas the sulfate and l-fucose contents increased by 16% and 71%, respectively. The biodistribution study in rat of both compounds labeled with (99m)Tc evidenced a predominant renal elimination of the purified fucoidan, but the crude fucoidan was mainly retained in liver and spleen. In rat myocardial ischemia-reperfusion, we then demonstrated the better efficiency of the purified fucoidan. This purified sulfated polysaccharide appears promising for the development of molecular imaging in acute coronary syndrome.